M. Alaggan
Reputation
331
Top tag
Next privilege 500 Rep.
Access review queues
 Mar 30 revised Proof of the diagonalization of the probability matrix of the sum of two binomial distributions edited tags Mar 30 revised Proof of the diagonalization of the probability matrix of the sum of two binomial distributions partial progress Mar 21 awarded Tumbleweed Mar 14 asked Proof of the diagonalization of the probability matrix of the sum of two binomial distributions Feb 26 awarded Excavator Feb 26 revised Lower bounds for inner product $x^\top y$ Changed >= to \geq Feb 26 suggested approved edit on Lower bounds for inner product $x^\top y$ Feb 24 comment Addition of two Binomial Distribution It has a special name: Poisson Binomial distribution. Feb 24 answered Addition of two Binomial Distribution Dec 19 comment Norm of a Matrix-vector product What is that inequality called? Dec 21 awarded Caucus Jul 2 awarded Curious Oct 1 accepted Can the measurement matrix used for compressive sensing be a sparse matrix? Sep 30 accepted Starting with $\frac{-1}{1}=\frac{1}{-1}$ and taking square root: proves $1=-1$ Sep 30 asked Can the measurement matrix used for compressive sensing be a sparse matrix? Sep 12 accepted Handshaking with no crossovers in minimum number of rounds: has this problem been studied? Aug 10 comment Starting with $\frac{-1}{1}=\frac{1}{-1}$ and taking square root: proves $1=-1$ But in this example, $e$, the base of the natural logarithm, is positive: $e^{z} \overset{!}{=} (e^{2\pi i})^{z/2\pi i} = 1^{z/2\pi i} = 1$ for all $z$. Is this an exception to the rule? Aug 8 comment Starting with $\frac{-1}{1}=\frac{1}{-1}$ and taking square root: proves $1=-1$ So is it always safe to distribute the root over products and quotients if ["the number insider the root is positive" $\vee$ "the root is odd"]? Is that the rule? Aug 7 comment Starting with $\frac{-1}{1}=\frac{1}{-1}$ and taking square root: proves $1=-1$ @ZevChonoles : The first question yes. But not the second question. Aug 7 comment Starting with $\frac{-1}{1}=\frac{1}{-1}$ and taking square root: proves $1=-1$ Can you elaborate on why is this a problem?